Proposed Digital Marketing Strategy To Recruit Tech-Talent For Company AX Indonesia - Aldo Nuari Imanuel (Program Studi Manajemen Institut Manajemen Koperasi Indonesia Bandung, 2023)
Company AX is a global leader in consulting, technology, and professional services. This dynamic organization continually seeks to enhance its tech talent pool in the highly competitive Indonesian market. However, it faces significant challenges in attracting and recruiting the right tech talents to support its operations and growth. The recruitment landscape in Indonesia is highly competitive, with numerous domestic and international players vying for tech talent. This project centers on addressing Company AX’s tech-talent recruitment challenges by leveraging digital marketing strategies. Digital marketing offers a promising avenue to engage with potential candidates, create brand awareness, and establish an effective recruitment funnel. With the exponential growth of the digital landscape, where candidates increasingly rely on online resources to explore career opportunities, it becomes vital for Company AX to establish a strong online presence and a compelling narrative to capture the attention of top tech talents. To analyze and understand the intricacies of Company AX’s tech-talent recruitment issue, a comprehensive framework has been adopted, namely VRIO, PESTLE, Porter’s Five Forces, and STP. This thorough analysis enables the identification of key obstacles and opportunities that inform the development of effective strategies. The implementation of solutions is guided by the RACE framework. RACE is employed for its proven effectiveness in structuring digital marketing initiatives. The framework provides a structured approach for Company AX to seamlessly reach out to potential tech talents, engage with them through captivating content, and ultimately guide them through a journey that converts their interest into applications. This research embraces the RACE framework as a robust methodology to construct a comprehensive digital marketing strategy that aligns with Company AX’s overarching tech-talent recruitment objectives. The findings and strategies developed through this project aim to serve as a blueprint for Company AX and other organizations facing similar recruitment challenges in Indonesia and beyond.